2019
DOI: 10.3390/molecules24162950
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Novel N-Acylhydrazone Bond Linked Heterobivalent β-Carbolines as Potential Anticancer Agents

Abstract: Utilizing a pharmacophore hybridization approach, we have designed and synthesized a novel series of 28 new heterobivalent β-carbolines. The in vitro cytotoxic potential of each compound was evaluated against the five cancer cell lines (LLC, BGC-823, CT-26, Bel-7402, and MCF-7) of different origin—murine and human, with the aim of determining the potency and selectivity of the compounds. Compound 8z showed antitumor activities with half-maximal inhibitory concentration (IC50) values of 9.9 ± 0.9, 8.6 ± 1.4, 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…[9] As a type dynamic covalent bond, an acylhydrazone bond is stronger than a hydrogen bond between molecules and has reversible properties under certain pH conditions (pH < 6.8) and can lead bond fracture at pH < 6.8. [26] Based on these unique properties, many studies have used acylhydrazone bonds to connect related compounds that can be separated in an acidic microenvironment (pH < 6.8). [27] The present study focused on the microenvironment of the in-…”
Section: Discussionmentioning
confidence: 99%
“…[9] As a type dynamic covalent bond, an acylhydrazone bond is stronger than a hydrogen bond between molecules and has reversible properties under certain pH conditions (pH < 6.8) and can lead bond fracture at pH < 6.8. [26] Based on these unique properties, many studies have used acylhydrazone bonds to connect related compounds that can be separated in an acidic microenvironment (pH < 6.8). [27] The present study focused on the microenvironment of the in-…”
Section: Discussionmentioning
confidence: 99%
“…Except for the BGC‐823 cell line, all of the examined tumor cell lines were more sensitive to the cytotoxic effects of hydrazone with a benzyl moiety at position 9 on β‐carboline. [ 82 ]…”
Section: N‐acylhydrazones As Anticancer Agentsmentioning
confidence: 99%
“…On the other hand, hydrazones (iNHN=C‐1) are known as biologically active fragements, which are widely used as a scaffold in agricultural chemistry . It has been reported that derivatives of hydrazones are shown to possess a wide range of biological activities, such as antifungal, antibacterial, insecticidal, herbicidal, antiviral and anticancer activities . Heretofore, some pharmaceutical companies have developed dozens of fungicides, insecticides, plant growth regulators such as benquinox, hydramethylnon and diflufenzopyr .…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] It has been reported that derivatives of hydrazones are shown to possess a wide range of biological activities, such as antifungal, antibacterial, insecticidal, herbicidal, antiviral and anticancer activities. [34][35][36][37][38][39] Heretofore, some pharmaceutical companies have developed dozens of fungicides, insecticides, plant growth regulators such as benquinox, hydramethylnon and diflufenzopyr. [40][41][42] All of the findings inspired us to design the bioactive structures with these functional motifs as potential agrochemical leads for plant disease control.…”
mentioning
confidence: 99%